Which radical expression is equivalent to 3^3/4

Answers

Answer 1
Answer: The numerator of the fraction is the power of the number and the denominator is the root of the number. This is expressed as follows:

⁴√(3)³
Answer 2
Answer:

Answer:27

Step-by-step explanation:


Related Questions

PLZ HEL P ME !!The question is based on the following circle graph. The graph represents the results of a survey in which 400 people were asked to identify the TV channel on which they preferred to watch the evening news. WKOD 13% WANR 22% WCLM 24% WWCN 41% write a ratio to express the number of people who preferred WANR to those who preferred WCLM A. 11 : 12 B. 23 : 100 C. 46 : 100 D. 3 : 50
Benito had 10 days of vacation. he spent 1/5 of his vacation fishing. he spent 30% of his vacation at soccer camp. he spent the rest of the time at the beach. what percent of his vacation did benito spend at the beach?
7. $65Alexis owed her brother $30. After her birthday, she was able to pay him back and still have $35. How much money did Alexis receive for her birthday?
What is the midpoint between (4,12) and (8,2)
PLEASEE HELP.!! ILL GIVE BRAINLIEST.!! *EXTRA POINTS* DONT SKIP:((

What is another way to write the ratio 3 to 10

Answers

Under ratio and proportion, there are a couple of ways you can use aside from using words to establish the relationship between 2 numbers.

One would be in a fraction form where "3 to 10" can be written as "3/10", or using a colon between the two numbers, where it would be written as "3:10". It is necessary to understand that these forms all mean the same, even if they look really different.

Using the following image, if you EG = 59, what are x, EF, and FG.

Answers

Answer:

x=6\,\,units\,,\,EF=34 \,\,units\,,\,FG=25\,\,units

Step-by-step explanation:

Given: EG =59 \,\,units

To find: x,EF,FG

Solution:

From the image, EG=EF+FG

Put EF=8x-14\,,\,FG=4x+1\,,\,EG=59

8x-14+4x+1=59\n12x-13=59\n12x=59+13\n\n12x=72\nx=(72)/(12)=6

EF=8x-14=8(6)-14=48-14=34\nFG=4x+1=4(6)+1=24+1=25

Therefore,

x=6\,\,units\,,\,EF=34 \,\,units\,,\,FG=25\,\,units

Find the second derivative for y=(x+2)/(x-3)

Answers

Let's find the first derivative.

Using quotient rule

f(x)=(g(x))/(h(x))

f'(x)=(g'(x)*h(x)-g(x)*h'(x))/(h^2(x))

then:

y=(x+2)/(x-3)
f(x)=y

g(x)=x+2

g'(x)=1

h(x)=x-3

h'(x)=1

Let's replace

f'(x)=(g'(x)*h(x)-g(x)*h'(x))/(h^2(x))

y'=(1*(x-3)-(x+2)*1)/((x-3)^2)

y'=(x-3-x-2)/((x-3)^2)

\boxed{y'=(-5)/((x-3)^2)}

the second derivative is the derivative of our first derivative.

y'=(-5)/((x-3)^2)

We can write this function as

y'=-5*(x-3)^(-2)

now we have to use the Chain rule's

f(u)=-5u^(-2)

and

g(x)=x-3

f[g(x)]=-5*(x-3)^(-2)

then

f'[g(x)]=f'(u)*g'(x)

f'(u)=-5*(-2)*u^(-3)=10*u^(-3)

g'(x)=1

f'[g(x)]=f'(u)*g'(x)

Let's replace

f'[g(x)]=10*u^(-3)*1

Let's change u by (x-3)

f'[g(x)]=10*u^(-3)

f'[g(x)]=10*(x-3)^(-3)

\boxed{\boxed{y''=(10)/((x-3)^(3))}}

......................................

Answers

Answer:

weight of one person + luggage=160pounds

the elevator supports 1200 pounds

maximum number of people in the elevator:

1200/160=7.5 or 7 people

Step-by-step explanation:

Students plan to pay back half the debt now though fundraising, and the rest after the harvest. Write an equation to represent the debt they will repay through fundraising. Use a negative integer to show debt. Use "D" to represent the debt that will be repaid by through fundraising

Answers

Answer:

D = (-d)/(-2)

Step-by-step explanation:

The amount of money that the students will pay back with the fundraiser (D) would be half of the current debt (d) since debt is represented as a negative but the fundraiser needs to be a positive since it is money gained we would divide by -2

D = (-d)/(-2)

This equation shows the debt that will be repaid through the fundraiser which would be exactly half of the current debt.

What is bigger 3 quarters or 5 eighths

Answers

Answer

3 quarters

Step-by-step explanation: